The Impact of Digital Learning on Creative Thinking Skills: A Case Study in Grade 12 at SMAIT Al-Multazam Kuningan - Handi Nuryaman; Septi Gumiandari (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This study aims to analyze the impact of digital learning on the creative thinking skills of Grade 12 students at SMAIT Al-Multazam Kuningan. This study used a qualitative approach with a case study design. Data collection was conducted through observation and in-depth interviews with five students selected using a purposive sampling technique based on their active involvement in digital learning. Data analysis was conducted using the interactive model of Miles and Huberman, which included the stages of data reduction, data display, and conclusion drawing. The results of the study showed that digital learning had a positive impact on students' creative thinking skills, as indicated by increased fluency in generating ideas, greater flexibility in developing alternative solutions, and greater originality in completing project-based tasks. The use of digital media, such as learning videos, visual media, and digital design platforms, serves as a stimulus that encourages broader exploration of ideas. The conclusion of this study shows that digital learning can be an effective strategy for developing students' creative thinking skills when supported by systematic learning planning and adequate technological infrastructure